Rancangan Penelitian dan Pengembangan (R & D) Pendidikan Agama Islam - Sumiati, Sumiati; Hermina, Dina; Salabi, Ahmad (FIKRUNA Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2023)
This article aims to find out how to determine the type of research and development (R&D) that is suitable for use in Islamic religious education research. The approach used in this research is a qualitative approach, with a descriptive research type. The framework used to analyze this theme is a thematic study based on research and development. Data analysis in this research is collecting literature related to R&D design and reviewing various relevant literature then analyzing it to answer the research focus. The discussions that will be raised are the meaning, objectives, characteristics, research and development (R&D) models (Sugiyono, Borg and Gall, 4D Development, and ADDIE Development). Each model has advantages and disadvantages in research, especially in Islamic Religious Education research. Research and development (R&D) is a research approach to produce new products or improve existing products. Research and development aims to discover, develop and validate a product. In the field of Islamic Religious Education, the products produced can be in the form of specific curricula for certain educational needs, teaching methods, educational media, textbooks, modules, educational staff competencies, evaluation systems, competency test models, classroom arrangements for certain learning models, models production units, management models, employee development systems, payroll systems and others.